Experimental Investigation of Wrap-Faced Reinforced Soil Embankments on Soft Clay: A Sustainable Solution for Infrastructure Development in Bangladesh - Hore, Shoma; Alim, Mosharof Al; Hore, Ripon (Department of Geography Education, University of Jember, Indonesia, 2025)
Wrap-faced reinforced soil retaining walls are a widely accessible solution globally, especially in areas where land use is a concern. The wrap-faced layer requires less space on both sides of the wall, making it a more economical and efficient option, and it is less vulnerable to dynamic loading. Incorporating dynamic loading in the design phase is crucial; however, current embankment projects in Bangladesh do not account for this aspect. Traditionally, sand embankments are constructed atop soft clay layers in road and railway embankment projects in Bangladesh. This research proposes the use of a wrap-faced embankment system on soft clay, piloted based on shake table test results conducted at the Bangladesh University of Engineering and Technology. Various governmental agencies, including the Roads and Highways Department, Local Government Engineering Department, and Bangladesh Railway, are involved in the construction of embankments, which typically require large land areas, especially for embankments with slopes of 1:2 or 1:3. This significant land requirement often becomes a limitation. In contrast, the wrap-faced embankment system offers a viable solution to the land scarcity issue, as it minimizes horizontal space usage and reduces construction costs compared to traditional embankments. This research details the proposed construction process and the modeling of the wrap-faced embankment system, offering insights into its potential for improving embankment design and land utilization in Bangladesh. The research evaluated the dynamic behavior of wrap-faced embankments on soft clay through PLAXIS 3D numerical modeling and shake table experimentation. The results indicated a consistent decrease in displacement with increased surcharge load. This confirms the potential of wrap-faced systems to enhance embankment stability during seismic events in Bangladesh.